Data Lake: Promoting a Home-Grown Tool for the Assessment Lifecycle - Shafer, Sharon M; Peterman, Dana S.; Grappone, Todd C. (Qualitative and Quantitative Methods in Libraries, 2022)
A recently created Library Strategic Plan at the University of California, Los Angeles (UCLA) identified the need to integrate a culture of assessment throughout the organization and to encourage data informed decision-making. This case study discusses the development of a home-grown tool that guides library staff in assessment activities, and acts as a central repository for assessment products. An appointed library team employed outreach and education techniques to teach assessment, but also helped to develop and to document assessment tools and resources. The team’s interaction with library staff, management, and campus assessment experts resulted in a flurry of discoverable library assessment studies, collection of associated data, and data applications and assets. Library-created studies and data have begun to deepen the understanding of assessment, and continuously improve the configuration of Data Lake. Dynamically generated reports using the features of Data Lake notify and insert resource managers at critical points in the assessment process and become part of an established project management lifecycle.